Application of Expert System in Rice Seedling Selection Based on Smart Data With Methods: Knowledge-Based System and Decision Tree - Santi Rahayu; Rosyani, Perani; Saputra, Riski Yoga; Umar, Restu Aji; Prasdio, Sendy; Syach, Wahyu Addiyan (International Journal of Integrative Sciences, 2025)
The selection of quality rice seeds is vital for maximizing agricultural productivity and sustainability. This study develops an expert system for rice seed selection based on intelligent data processing using the Knowledge-Based System (KBS) and Decision Tree methods. KBS encodes expert knowledge to evaluate seed quality and environmental compatibility, while Decision Tree algorithms classify and predict optimal seed choices. Experimental results demonstrate the system's accuracy in recommending suitable seeds, reducing selection time and effort. This research highlights the potential of artificial intelligence in enhancing decision-making processes in modern agriculture.